Ideology through Modalities: Can the Translator Preserve Them? - Nuning Yudhi Prasetyani; Mangatur Rudolf Nababan; Djatmika Djatmika; Joko Nurkamto (Universitas Airlangga, 2019)
The study explores on the application of modality reflecting the ideology by the author, Dale Carnegie, in ‘How to tn Friends and Influence People’ book and how the translator rendered them through the selection of translation techniques into Bagaimana Mencari Kawan dan Mempengaruhi Orang Lain . By carrying Teun A. Van Dijk’s socio-cognitive model in determining the ideology and Simpson’s Language, Ideology and Point of View in determining the modality, we analyse the ideological expressions applied through the modalities and the Indonesian translated version. Dijk’s model was chosen since it represents the genre of this book that he brings a great theme to his ideology by directing it to social cognition. The modalities found in this research are epistemic, boulomaic, evaluative adjective, evaluative adverb and deontic. These modalities were translated into Indonesian using 10 (ten) translation techniques initiated by Molina & Albir (2002) and rated with the model of translation quality assessment from Nababan et al. (2012). The techniques which lead to the good of translation quality were established equivalent, transposition, amplification, (obligatory) modulation, and compensation. In general, the translator has been able to render the author's ideology manifested in modalities by applying these translation techniques. Thus, translator’s competency in choosing the right translation techniques shows his or her capability in comprehending the context of situation, elements of ideology in accordance with the genre, function and communicative purpose of the text.